Methionine synthase, a gene required for methionine synthesis, is expressed in planta by Cladosporium fulvum - Solomon, P.; Nielsen, P.; Clark, A.; Oliver, Richard (2000)
The nutritional requirements of phytopathogenic fungi growing in planta has to date been largely ignored. We have begun to address this problem by investigating the methionine requirement for the biotrophic pathogen of tomato Cladosporium fulvum during infection. The Met6 gene from Cladosporium fulvum encoding a cobalamin-independent 5-methyltetrahydropteroyltriglutamate-homocysteinemethyltransferase, was cloned by functional yeast complementation. The open reading frame was found to be 2304 bp, containing no introns and encoding a protein of 87 kDa. In vitro Northern analysis demonstrated high levels of Met6 expression in the absence of externally supplied methionine. However in the presence of methionine or in the absence of carbon, expression of Met6 decreased significantly. Analysis of Met6 expression in planta revealed a strong increase during infection suggesting the requirement for methionine synthesis in planta by Cladosporium fulvum. This study demonstrates that Cladosporium fulvum is starving for methionine during infection and thus implies the essentiality of primary biosynthetic pathways to the infecting fungus.